Status of key faunal species in Koshi Tappu Wildlife Reserve after Koshi flood disaster 2008 - Limbu, Kul Prasad; Subba, Bhara Raj (Nepalese Journal of Biosciences, 2013)
Present survey was carried out from April 16th to December 15th of 2009 with a view to assess the key faunal species of Koshi Tappu Wildlife Reserve such as Birds, Gangetic Dolphin, Wild water buffalo, different species of fish and their habitats after Koshi flood disaster 2008. Several trips were made within the KTWR using boat for surveying dolphin census, to make checklist of birds and fishes and to study wild water buffalo status. Among 120 species of birds belonging to 44 families and 103 genera were sighted, 27 species were found as winter visitor, 4 species as summer visitor and 89 species as resident birds. The census of Gangetic Dolphin was conducted in the Koshi river course starting from Rajabas to Koshi Barrage (36 km) in November-December 2009. The census concluded with a sighting of 6 dolphins in the river section north of Koshi Barrage upto Rajabas and 5 dolphins in the downstream of Koshi Barrage. The status of wild water buffalo was also studied in different areas of KTWR. Regular collection of fish enlisted 64 species belonging to 15 families and 40 genera. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7469 Nepalese Journal of Biosciences 1: 41-54 (2011)